Matriz do fluxo de comércio interestadual dos estados do Ceará, Paraná e Mato Grosso: uma análise comparativa do período de 2011 a 2016 - Lima Junior, Olavo Pereira de (2017)
The present work aims at analyzing the dynamics of interstate trade flow covering the states of Ceará, Paraná and Mato Grosso for the period from 2011 to 2016. The data base used was from the electronic invoices which was confirmed in the study that such data were rather rich for economic analysis. It has made possible the identification of the most important Brazilian regions with regards to interstate operations within the states targeted by this research. It was also possible to identify the economic activities profile from the participants in the commercial relationship. Also it was possible to establish the degree of technical intensity of commercialized products based on the OECD (Organization for Economic Cooperation and Development) classification. As a main result, it was verified that the states of Ceará and Mato Grosso present similar profiles of developing states, due to the fact that they import products classified as medium-high technological intensity and export low technological intensity products. Regarding the state of Paraná, it has been identified that its interstate entry operations, within the length of time analyzed, have been migrating from medium-high to low technological intensity products. As to the sales (exit) operations, it was also observed this trend to a growth in sales of medium-high products, as a consequence of a decrease in low technological intensity products. This has shown evidences that the state of Paraná has evolved to a developed state level. Finally, it was verified the strong commercial relationship of the three states with the Southeast region, showing a significant degree of dependency, mainly to the State of São Paulo. Within the second level, it was verified that the state of Ceará has a strong commercial relationship with the Northeast region, while the states of Paraná and Mato Grosso with the South region.